GaN-based materials and devices : growth, fabrication, characterization and performance - Shur, Michael; Davis, Robert F. (Robert Foster), 1942- (River Edge, N.J. ; London : World Scientific., 2004)
The unique materials properties of GaN-based semiconductors have stimulated a great deal of interest in research and development regarding nitride materials growth and optoelectronic and nitride-based electronic devices. High electron mobility and saturation velocity, high sheet carrier concentration at heterojunction interfaces, high breakdown field, and low thermal impedance of GaN-based films grown over SiC or bulk AIN substrates make nitride-based electronic devices very promising. The chemical inertness of nitrides is another key property. This volume, written by experts on different aspects of nitride technology, addresses the entire spectrum of issues related to nitride materials and devices, and it will be useful for technologists, scientists, engineers, and graduate students who are working on wide bandgap materials and devices. The book can also be used as a supplementary text for graduate courses on wide bandgap semiconductor technology.
Materials Properties of Nitrides. Summary/ S.L. Rumyantsev, M.S. Shur, and M.E. Levinshtein -- Kinetics, Microstructure and Strain in GaN Thin Films Grown Via Pendeo-Epitaxy/ A.M. Roskowski, E.A. Preble, S. Einfeldt, P.M. Miraglia, J. Schuck, R. Grober, and R.F. Davis -- Strain of GaN Layers Grown Using 6s-SiC(OOO1) Substrates with Different Buffer Layers/ S. Einfeldt, Z.J. Reitmeier, and R.F. Davis -- Growth of Thick GaN Films and Seeds for Bulk Crystal Growth/ P.R. Tavernier, E.V. Etzkorn, and D.R. Clarke -- Cracking of GaN Films/ E.V. Etzkorn and D.R. Clarke -- Direct Bonding of GaN and Sic; A Novel Technique for Electronic Device Fabrication/ J. Lee, R.F. Davis, and R.J. Nemanich -- Electronic Properties of GaN(0001) -- Dielectric Interfaces/ T.E. Cook, Jr., C.C. Fulton, W.J. Mecouch, R.F. Davis, G. Lucovsky, and R.J. Nemanich -- Quasi-Ballistic and Overshoot Transport in Group 111-Nitrides/ K.W. Kim, V.A. Kochelap, V.N. Sokolov, and S.M. Komirenko -- High Field Transport in AlN/ R. Collazo, R. Schlesser, and Z. Sitar -- Generation-Recombination Noise in GaN-Based Devices/ S.L. Rumyantsev, N. Pala, M.S. Shur, M.E. Levinshtein, R. Gaska, M. Asif Khan, and G. Simin -- Insulated Gate 111-N Heterostructure Field-Effect Transistors/ G. Simin, M. Asif Khan, M.S. Shur, and R. Gaska -- High Voltage AIGaN/GaN Heterojunction Transistors/ L.S. McCarthy, N-Q. Zhang, H. Xing, B. Moran, S. DenBaars, and U.K. Mishra -- Etched Aperture GaN Cavet Through Photoelectrochemical Wet Etching/ Y. Gao, I. Ben-Yaacov, U. Mishra, and E. Hu -- n-AlGaAs/pGaAs/n-GaN Heterojunction Bipolar Transistor: The First Transistor Formed Via Wafer Fusion/ S. Estrada, E. Hu, and U. Mishra.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Gallium nitride; Semiconductors -- Materials; Nitrure de gallium; Semi-conducteurs -- Matériaux.; TECHNOLOGY & ENGINEERING -- Electronics -- Solid State; TECHNOLOGY & ENGINEERING -- Electronics -- Semiconductors; Gallium nitride; Semiconductors -- Materials; Gallium nitride; Semiconductors -- Materials